Celebrity endorsements and branding strategies: event study from India. Issue 6 (21st September 2015) - Jaikumar, Saravana; Sahay, Arvind
Abstract : Purpose: – The purpose of this study is to evaluate the economic value of celebrity endorsements to Indian firms based on their branding strategy – corporate or house-of-brands – and their "congruence" or "fit" with the celebrity. The overall economic value of endorsements to firms in India, a moderately collectivist culture, is also assessed. Design/methodology/approach: – Standard "event study" methodology is used to evaluate the economic value of endorsements under different branding strategies (47 endorsement announcements – 25 corporate brands and 22 house-of-brands). The impact of the level of congruence (assessed using brand personality scales) on abnormal returns is also examined. Findings: – Event study results indicate significant positive abnormal returns for corporate brands and insignificant returns to house-of-brands. Moreover, the level of congruence is found to have an insignificant effect on endorsement announcement returns. Overall, celebrity endorsements result in positive economic value to Indian firms. Originality/value: – This study evaluates the differences in the effectiveness of celebrity endorsements (which might form a significant part of advertising costs) to firms following different branding strategies. Findings from this study indicate that celebrity endorsement announcements from house-of-brands do not lead to any significant stock market returns (in terms of market value). Further, contrary to current literature, the results indicate that the congruence between brand and celebrity has no impact on returns to endorsements in India, warranting further examination of whether congruence or likeability is important in endorsements.